Clima del aula y el comportamiento en estudiantes del sexto ciclo de educación secundaria del Ceba Miguel Acosta Oyarce, Caballococha 2024 - Vasquez Gutierrez, Leunard (2024)
The purpose of this research is to determine the relationship between the level of classroom climate and the level of behavior in students of the sixth cycle of secondary education at CEBA Miguel Acosta Oyarce, Caballococha 2024, the type of research is quantitative, non-experimental study, correlational design, transectional design; The population under study is made up of students from the sixth cycle of the EBR, from the first and second grades of secondary school. The techniques that will be used in data collection will be the survey. and observation, which are validated by three experts in the field, resulting in a Spearman correlation coefficient of 0.732, which indicates a high positive correlation between classroom climate and student behavior. This value is significant with p = 0.05, which suggests that there is a statistically significant relationship between both variables. The null hypothesis is rejected and the general hypothesis is accepted. This confirms that the level of the classroom climate is related to the level of behavior of the students of the sixth cycle of secondary education at the CEBA Miguel Acosta Oyarce, Caballococha, 2024.